Skorupki tradycji. Portret elastycznego hindusa - Ciemniewski, Marcin (Studia Azjatystyczne, 2017)
Stereotypically India is seen as a very spiritual country. The same applies to Indians, especially Hindus. The main aim of this article is to answer the question whether the spirituality of Hindus and their perception of tradition have changed or have taken a new form under the influence of the rapidly changing times. This article examines the ways of looking at tradition by modern Hindus especially those who represent the Indian middle class by reading an one-act play The Eggshells (A !ekechilke) by Mohan Rakesh and an essay by Sudhir Kakar and Katharina Kakar entitled The Flexible Hindu.